Analyzing Corin–BNP–NEP Protein Pathway Revealing Differential Mechanisms in AF-Related Ischemic Stroke and No AF-Related Ischemic Stroke - Xiaozhu Shen; Xiaozhu Shen; Nan Dong; Nan Dong; Yiwen Xu; Lin Han; Rui Yang; Juan Liao; Xianxian Zhang; Tao Xie; Yugang Wang; Chen Chen; et al. (Frontiers in Aging Neuroscience, 2022)
BackgroundThe incidence of atrial fibrillation (AF)-related stroke increases with aging. Natriuretic peptides (NPs) family, including Corin-B type natriuretic peptide (BNP)-neprilysin (NEP) protein levels increased with age and are risk markers of cardiovascular and cerebrovascular diseases, such as AF and cardioembolic stroke. Aging is also linked to epigenetics, specifically DNA methylation. However, only a few studies have investigated the effect of DNA methylation on the NP system. Thus, the present study aimed to investigate whether the Corin-BNP-NEP protein pathway is involved in the pathogenesis of AF-stroke and CpG methylation in the promoter region of the Corin protein gene has an effect on AF-related ischemic stroke.MethodsA total of 82 patients hospitalized with acute ischemic strokes were enrolled in this study. The differences in clinical information were compared between the AF-stroke (n = 37) and no AF-stroke groups (n = 45). Plasma-soluble Corin and NEP were detected using an ELISA kit. CpG methylation in the promoter region of the gene was assessed by a next-generation sequencing-based bisulfite sequencing polymerase chain reaction (BSP).Results(1) Patients in AF-stroke were older, had higher initial NIHSS score, 90-day mRs, higher D2-dimer, INR, and APTT, and low TG, TC, and HbA1c (all p < 0.05). (2) Serum levels of Corin and BNP in the AF-stroke group were significantly higher than that in the no AF-stroke group (p < 0.05). No significant difference was detected in the serum levels of NEP between the two groups. (3) The levels of CpG methylation in the promoter region of the Corin protein gene in the AF-stroke group was significantly lower than that in the no AF-stroke group (p < 0.05). The CpG sites with maximal methylation differences between the two groups were CORIN:678, CORIN:682, CORIN:694, and CORIN:700.ConclusionThe current findings raise the possibility that the Corin–BNP–NEP protein pathway may be involved in the pathogenesis of AF-related ischemic stroke. Deficient CpG methylation in the promoter region of the Corin protein gene is associated with AF-related ischemic stroke.